Integrated Educational System – Pure Experiment or Model for the Future - Dušan Vasić; Aleksandra Stojković; Bojan Zdravković (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Dubrovnik, Croatia, 7-9 September 2017, 2017)
The use of the term "integrated" in the sphere of education always refers to higher education, namely the studies involving basic academic studies and master academic studies. However, in contrast to this notion of "integration," in Serbia a sui generis model of integrated education has been developed. The model goes beyond the scope of known structure of integration and spreads both vertically and horizontally. It gathers institutions at all levels of education – starting with preschool, elementary, secondary, high and higher school education, and ending with the doctoral studies. At first sight, this new legal solution resembles a kind of educational industry holding. Of course, such new system faces certain difficulties and misunderstandings, being pretty different from both the classic and modernistic one. This is quite an unusual system, both in legal terms and terms of organization and management. Some will look at it as an experiment, for which they do not know whether it would hold out the test of time, but those who have created it, consider it an educational model of the future. In this article, we present "Integrated Educational System for Social and Natural Sciences" from Belgrade, as a case study, explaining its structure, regulation, organization and characteristics, as well as the challenges it faces. Our intention is to share with the Conference participants the experience, thoughts and observations about such a remarkable venture and discuss the lessons learned.
Keywords: I20; 330; Integrated studies; undergraduate studies; master studies; education system